2019
DOI: 10.1155/2019/1729013
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Cyclophilin D Attenuates Oxidative Stress-Induced Cell Death in Human Dental Pulp Cells

Abstract: Pathological stimuli, such as bacterial activity, dental bleaching, and nonpolymerized resin monomers, can cause death of dental pulp cells (DPCs) through oxidative stress- (OS-) induced mitochondrial dysfunction. However, the crucial molecular mechanisms that mediate such a phenomenon remain largely unknown. OS is characterized by the overproduction of reactive oxygen species (ROS), e.g., H2O2, O2−, and ⋅OH. Mitochondria are a major source of ROS and the principal attack target of ROS. Cyclophilin D (CypD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The different treating condition of the compounds were as follows: H 2 O 2 (0.1-1 mM, Sigma, United States) for 6 h, Cur (0.25 µM, Sigma, United States) for 24 h, TDZD-8 (5 µM, Sigma, United States) for 1 h, tBHQ (5 µM, Sigma, United States) for 1 h, NAC, the widely used antioxidant for positive control (2.5 mM, Sigma, United States) for 1 h, according to previous studies (Dai et al, 2017;Cuadrado et al, 2018;Huang et al, 2019) and our preliminary data (data not shown). Cells were treated with or without H 2 O 2 and the indicated compounds for various conditions in basic medium or osteogenesis differentiation medium.…”
Section: Cell Treatmentmentioning
confidence: 99%
“…The different treating condition of the compounds were as follows: H 2 O 2 (0.1-1 mM, Sigma, United States) for 6 h, Cur (0.25 µM, Sigma, United States) for 24 h, TDZD-8 (5 µM, Sigma, United States) for 1 h, tBHQ (5 µM, Sigma, United States) for 1 h, NAC, the widely used antioxidant for positive control (2.5 mM, Sigma, United States) for 1 h, according to previous studies (Dai et al, 2017;Cuadrado et al, 2018;Huang et al, 2019) and our preliminary data (data not shown). Cells were treated with or without H 2 O 2 and the indicated compounds for various conditions in basic medium or osteogenesis differentiation medium.…”
Section: Cell Treatmentmentioning
confidence: 99%
“…Then, 16 studies were excluded, and the reasons for their exclusion can be found in Figure 1 and Supplementary Data 1 [ 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. Twenty-seven studies meeting the inclusion criteria were selected for qualitative analysis [ 1 3 6 11 12 17 23 24 25 26 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 presents data from 19 in vitro studies that explored various agents aimed at reducing cytotoxicity during the bleaching process [ 6 23 24 45 46 47 48 49 50 51 52 53 54 55 56 57 ]. The majority of these studies utilized human dental pulp cells (HDPCs) and mouse dental papilla Cell-23 (MDPC-23) cells, with each cell type being used in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…MtROS is an widely accepted initiator of apoptosis through numerous mechanisms, and it is not only related to damage of mitochondrial function, but also leading to an apoptotic signaling pathway cascade [9] [33] [34] . Notably, as the products of mitochondrial metabolism, mtROS comes from the respiratory chain when mitochondria are functionally disordered [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play vital roles in many cellular processes including cell proliferation, metabolism and apoptosis [9] [10] [11] . Accumulating evidence has implicated excess reactive oxygen species (ROS) in mitochondria promote caspase-dependent apoptosis, so mitochondria are identi ed as the center of apoptosis through the intrinsic pathway [12] .…”
Section: Introductionmentioning
confidence: 99%